Identification and management of malnutrition in hospitalised patients: A survey of staff knowledge and attitudes. (June 2020) - Swan, Indi; Nyulasi, Ibolya; Collins, Kathryn; Weir-Phyland, Janet; Bolster, Danielle; Burgell, Rebecca; Fineberg, Daniel; Johnson, William; King, Susannah; Leong, Ronald; McLachlan, Gary; Murnane, Lisa; et al.
Summary: Background & aims: Malnutrition is associated with functional decline and poorer clinical outcomes for hospitalised patients. This study aimed to survey the knowledge of clinical staff concerning identification/diagnosis and management of inpatient malnutrition and to assess attitudes and knowledge of malnutrition as a shared inter-disciplinary responsibility. Methods: A survey designed to investigate the aims was distributed to clinical staff (medical, nursing, dietitians and allied health) across three hospital campuses including acute, sub-acute and rehabilitation sites. Results: Survey responses were received from 14% (n = 302) of eligible clinical staff (116 nursing, 68 medical, 20 dietitians and 98 other allied health staff). With the exception of dietitians, responses to questions regarding skills and knowledge in the areas of malnutrition identification, diagnosis, treatment and management indicated sub-optimal knowledge. Only 60% of medical/surgical staff and 42% of nursing staff self-reported the ability to diagnose malnutrition. Responses to questions regarding responsibility for malnutrition were highly variable and suggested no significant 'shared ownership' of malnutrition as clinical responsibility. Conclusion: Apart from dietitians, malnutrition management skills were modest and knowledge gaps of clinical staff were marked. Confusion also existed as to the responsibility for malnutrition care for inpatients. To improve inpatient nutrition further multidisciplinary engagement and improved education may be required.